25.9k views
2 votes
10(1 -8b) = 10b + 5(b + 2)

1 Answer

2 votes

Answer:

b = 0

Explanation:

Step 1: Write equation

10(1 - 8b) = 10b + 5(b + 2)

Step 2: Solve for b

  1. Distribute: 10 - 80b = 10b + 5b + 10
  2. Combine like terms: 10 - 80b = 15b + 10
  3. Add 80b to both sides: 10 = 95b + 10
  4. Subtract 10 on both sides: 0 = 95b
  5. Divide both sides by 95: 0 = b
  6. Rewrite: b = 0

Step 3: Check

Plug in b to verify it's a solution.

  1. Substitute: 10(1 - 8(0)) = 10(0) + 5(0 + 2)
  2. Evaluate: 10(1 - 0) = 0 + 5(2)
  3. Evaluate: 10(1) = 10
  4. Evaluate: 10 = 10
User Atconway
by
7.5k points